2021
DOI: 10.1186/s12871-021-01520-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and prognosis in patients with urosepsis from intensive care unit in Shanghai, China: a retrospective bi-centre study

Abstract: Background The purpose of this study was to retrospectively analyze clinical characteristics and prognostic risk factors of urosepsis patients admitted to two intensive care units in Shanghai, China. Methods Clinical data from patients diagnosed with urosepsis were retrospectively retrieved and analyzed from ICU in two regional medical centers from January 2015 to December 2019. Results Two hundred two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
2
3
0
1
Order By: Relevance
“…The median age of our patients (67 years) was identical with the Canadian survey; although, in our study, most patients were male [ 24 ]. In a 2-center study from China, the age structure of patients was similar to that of our present study, but the number of women affected was higher [ 25 ]. It is also interesting that, in contrast to our study in which the most common urological comorbidity disease was hydronephrosis (due to the dysfunction of urinary drainage), in the case of the study from China, it was urolithiasis [ 25 ].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The median age of our patients (67 years) was identical with the Canadian survey; although, in our study, most patients were male [ 24 ]. In a 2-center study from China, the age structure of patients was similar to that of our present study, but the number of women affected was higher [ 25 ]. It is also interesting that, in contrast to our study in which the most common urological comorbidity disease was hydronephrosis (due to the dysfunction of urinary drainage), in the case of the study from China, it was urolithiasis [ 25 ].…”
Section: Discussionsupporting
confidence: 77%
“…In a 2-center study from China, the age structure of patients was similar to that of our present study, but the number of women affected was higher [ 25 ]. It is also interesting that, in contrast to our study in which the most common urological comorbidity disease was hydronephrosis (due to the dysfunction of urinary drainage), in the case of the study from China, it was urolithiasis [ 25 ]. A study from Ireland showed a similar average age (70 years) and more female patients (60%) [ 28 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In urosepsis patients, organ function and Lac clearance are impaired, which also leads to elevated serum Lac. 71 Lac is an independent risk factor for death in patients with urosepsis 20 and is closely related to patient prognosis. Lac levels have long been used in sepsis screening and management to help physicians make clinical decisions.…”
Section: Lactic Acid (Lac)mentioning
confidence: 99%
“…An inappropriate antibiotic therapy increases the risk of antibiotic resistance [4], and it is a financial burden for the community [5]. Conversely, a delay of an appropriate treatment could impact patient conditions, considering that mortality rates due to urosepsis can be as high as 16% [6]. Consequently, there is a strong need for biomarkers able to ease the clinical diagnosis of UTIs.…”
Section: Introductionmentioning
confidence: 99%